WY195, a New Inducible Promoter From the Rubber Powdery Mildew Pathogen, Can Be Used as an Excellent Tool for Genetic Engineering - Wang, Yi; Wang, Chen; Rajaofera, Mamy Jayne Nelly; Zhu, Li; Xu, Xinze; Liu, Wenbo; Zheng, Fucong; Miao, Weiguo (Frontiers in Microbiology, 2020)
Until now, there are few studies and reports on the use of endogenous promoters of obligate biotrophic fungi. The WY195 promoter in the genome of Oidium heveae, the rubber powdery mildew pathogen, was predicted using PromoterScan and its promoter function was verified by the transient expression of the -glucuronidase (GUS) gene. WY195 drove high levels of GUS expression in dicotyledons and monocotyledons. qRT-PCR indicated that GUS expression regulated by the WY195 promoter was 17.54-fold greater than that obtained using the CaMV 35S promoter in dicotyledons (Nicotiana tabacum), and 5.09-fold greater than that obtained using the ACT1 promoter in monocotyledons (Oryza sativa). Furthermore, WY195-regulated GUS gene expression was induced under high-temperature and drought conditions. Soluble proteins extracted from WY195-hpaXm transgenic tobacco was bioactive. Defensive micro-HR induced by the transgene expression of hpaXm was observed on transgenic tobacco leaves. Disease resistance bioassays showed that WY195-hpaXm transgenic tobacco enhanced the resistance to tobacco mosaic virus (TMV). WY195 has great potential for development as a new tool for genetic engineering. Further in-depth studies will help to better understand the transcriptional regulation mechanisms and the pathogenic mechanisms of O. heveae.